PENDETEKSI TANAH LONGSOR MENGGUNAKAN SENSOR CAHAYA - Sudibyo, Novi Herawadi; Ridho, Muhammad (244-5567)
Landslide disasters are the events in movement soil or rock mass with a certain amount of various types and kinds such as landslides translational, rotational landslides and ground creep. Landslides may occur if the driving style on a slope greater than the retaining force, the number of victims resulting from natural disasters due to landslide disasters occur suddenly. Needed a tool that can help provide early warning of natural disasters landslides are sudden. With thismicrocontroller consists of two this part, that this part potentiometer sensor, LDR (Light Dependent Resistor) to read the the shift ground and part wavecom modem as an early warning sign.Keywords: Microcontroller (Arduino), Sensor Light, Natural Disasters, of Early Warning